Consumer Purchase Intention: A Study based on Content Marketing, Consumer Value - Liu, Yue (International Journal of Social Sciences and Public Administration, 2024)
The development of digital economy has put forward new requirements for the sustainability of content marketing. Short video content has gradually entered people ’s vision and attracted more and more people ’s attention. Based on this, this study analyzes the influencing factors of content marketing, consumption value and consumer purchase intention of short video platform, aiming to clarify the current situation of short video content marketing, grasp the characteristics of short video marketing, tap the potential of consumer purchase intention, and improve the marketing quality of short video. Provide advice and suggestions to meet the diverse needs of users to consumers.